Opto-electroactive amino- and pyridyl-terminated monolayers of ruII-terpyridyl complexes and their usage as Hg2+ sensors - Mondal, Prakash Chandra; Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2019)
Robust opto-electroactive monolayers of three different RuII-terpyridyl complexes with amino and pyridyl termination are fabricated on SiOx-based substrates using siloxane-based attachment chemistry and either pyridyl or amine linkage to the preliminary prepared template. The UV-vis spectra of these monolayers display the characteristic metal-to-ligand charge-transfer bands, with a bathochromic shift compared to the spectra of the respective metalloligands dissolved in acetonitrile solution. This shift is notably larger for the pyridyl-linked monolayers compared to the amino-linked film, correlating qualitatively with the molecular grafting density. Cyclic voltammograms of the monolayers covalently attached onto indium tin oxide electrodes show reversible switching between the two redox states (Ru2+ to Ru3+ and vice versa), with a typical one-electron redox behavior. The sensing response of the monolayers to a series of different metal ions was tested, with the amino-decorated films showing a particularly high sensitivity to Hg2+ and a close-to-linear response to this analyte in the ppm concentration range.